Scenario thinking pathways to the future - Sangster, Deborah; Neal, Brad (Minnesota : Compass Films International, 1995)
An explaination of scenario thinking by Clem Sunter, the Chairman of the Gold and Uranium Mining Division of the Anglo American Corporation of South Africa
Copy available in DVD format
Author, Clem Sunter
Host: Clem Sunter
Keywords: Thought and thinking; Management